Studying the Enrichment of Ice Cream with Alginate Nanoparticles Including Fe and Zn Salts. (4th April 2013) - Sharifi, Armoon; Golestan, Leila; Sharifzadeh Baei, Mazyar
Abstract : The aim of this research was developing alginate nanoparticles as a carrier for food enrichment. In this research, Fe/Zn-loaded alginate nanoparticles were prepared and characterized as point size, morphology, FTIR, loading efficacy (LE), and release properties and used in ice cream structure. After this stage, absorption of the salts was measured and sensory and rheological evaluations were taken for samples. Results showed that alginate nanoparticles have average size between 90 and 135 nm. Also, the shape of the nanoparticles is regular and smooth without aggregation phenomena. FTIR certified that Zn/Fe loaded into alginate nanoparticles. Also, loading efficacy of Zn/Fe was 70–85% and release profile of nanoparticles showed a steady state. Alginate nanoparticles could decrease the loss of Fe/Zn in comparison control. Furthermore, these nanoparticles have no side effects on sensory and rheological properties. Hence, this nanoparticle can be suggestive for the enrichment of ice cream and probably other foods.